2009
DOI: 10.1099/vir.0.010330-0
|View full text |Cite
|
Sign up to set email alerts
|

Complete genomic sequences for hepatitis C virus subtypes 4b, 4c, 4d, 4g, 4k, 4l, 4m, 4n, 4o, 4p, 4q, 4r and 4t

Abstract: Short CommunicationComplete genomic sequences for hepatitis C virus subtypes 4b, 4c, 4d, 4g, 4k, 4l, 4m, 4n, 4o, 4p, 4q, 4r and 4t In this study, we characterized the full-length genomic sequences of 13 distinct hepatitis C virus (HCV) genotype 4 isolates/subtypes: QC264/4b, QC381/4c, QC382/4d, QC193/4g, QC383/ 4k, QC274/4l, QC249/4m, QC97/4n, QC93/4o, QC139/4p, QC262/4q, QC384/4r and QC155/4t. These were amplified, using RT-PCR, from the sera of patients now residing in Canada, 11 of which were African i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 46 publications
1
24
0
1
Order By: Relevance
“…Like these, the novel genotype 4 variant evolved probably from a common ancestor originating in Africa. The genetic variation between these subtypes and the strains found in this study (17-19%) is smaller than the criteria for subtype discrimination [Simmonds et al, 2005], but they belong to distinct subtypes, representing the epidemiological associations of these variants and indicating possibly a continual genetic variation of HCV with many variants still missing [de Bruijne et al, 2009;Li et al, 2009]. Epidemiologically distinct infections of this variant have been found in patients of African origin in Canada, Britain, and Denmark [Murphy et al, 2007;Demetriou et al, 2009;Eriksen et al, 2010], and in this study two near-full genome reference sequences of this novel type are presented for the first time.…”
Section: Discussionmentioning
confidence: 88%
“…Like these, the novel genotype 4 variant evolved probably from a common ancestor originating in Africa. The genetic variation between these subtypes and the strains found in this study (17-19%) is smaller than the criteria for subtype discrimination [Simmonds et al, 2005], but they belong to distinct subtypes, representing the epidemiological associations of these variants and indicating possibly a continual genetic variation of HCV with many variants still missing [de Bruijne et al, 2009;Li et al, 2009]. Epidemiologically distinct infections of this variant have been found in patients of African origin in Canada, Britain, and Denmark [Murphy et al, 2007;Demetriou et al, 2009;Eriksen et al, 2010], and in this study two near-full genome reference sequences of this novel type are presented for the first time.…”
Section: Discussionmentioning
confidence: 88%
“…The HCV genotype 4 has 19 assigned subtypes (a-h and k-u) (24). This genotype is highly prevalent in the Middle East (Teheran, Yemen, Kuwait, Iraq, and Saudi Arabia) and in Africa, particularly in Egypt due to the use of unsterile equipment during mass treatment of the population with parenteral antischistosomal therapy from the 1920s to the 1980s (7,13,15,18).…”
Section: Discussionmentioning
confidence: 99%
“…These isolates appear to represent a new subtype. They should be analyzed in another region of the viral genome, especially in the hyper variable region E1/E2 which, according to many authors, would best reflect the full extent of subtype variations present in the infected individuals (16) or better yet by sequencing the whole genome (24,44).…”
Section: Discussionmentioning
confidence: 99%
“…Based on full-length genome sequence data from our previous study, a total of 17 HCV-4 subtypes (4a–4d, 4f, 4g, 4k–4r, 4v, 4w) are now confirmed (Li et al, 2009; Smith et al, 2014). Two distinct HCV-4 variants not assigned to a subtype also have had their genomes completely sequenced.…”
Section: Introductionmentioning
confidence: 95%